Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content: 1. The role of social media in promoting entrepreneurship and innovation among youth in Saudi Arabia (A Field Study) Mr. Ahmad Abdrabuh Al-Tamimi 2. NATO strategy for 2010 and its implications for the Arab world Ms. Enas Ahmed Abdullah 3. The Role of Green Sukuk in Achieving the Sustainable Development Goal of Climate Action: The Case of Saudi Arabi (2020-2025) Dr. Abdulrhman Mohmmad Alamoudi , Ms. Sheikha Mahisn Alhasani ,Ms. Nada Mohammed Bahakim 4. Portfolio Analysis: Performance and Risk Strategies Ms. Rwaida Saeed Suliman 5. The environmental impact of living cultural heritage (intangible heritage) and its role in reducing unemployment in the local community of Khyber Mr. Eyad Anwar Naqshabandi, Co-Pof. Nabil Tarifi 6. The Impact of Artificial Intelligence on the Scope of Internal Audit: A Comparative Study Between Population-Based and Sample-Based Approaches Mr. Ahmed Farouk Ali 7. Incentive of job stability and its relationship to the performance of the worker in the industrial establishment: The case of Sarmook Company for Oriental Drinks, Setif, Algeria Ms. Rafika Benmansour